A NEW SCRAMBLE? GEOPOLITICAL ECONOMY OF MULTI-POLARITY IN THE SAHEL AND ITS IMPLICATIONS FOR AFRICA’S ECONOMIC SOVEREIGNTY - Okoli, Al Chukwuma; Alhassan, Abdulkareem (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
This study explores how the Sahel has emerged as a contested space for influence, competitive stakes, resources, and markets. The paper posits that the Sahel’s geopolitical economy is characterized by a new scramble – a multi-polar struggle by the global and regional powers – for dominance and strategic advantage, with far-reaching implications for the sovereignty of the member states as well as regional stability and development. The paper underscores the nuanced issues that underpin the evolving geopolitical landscape in the Sahel and what they hold African agency and sovereign virtues, especially in the realms of economy and geo-strategy. Keywords: Geopolitics, global powers, multi-polarity, political economy, sovereignty, the Scramble.